Phytochemical and Antibacterial Screening of Chromolaena odorata Leaf Extract - Norlizawati, Ishak; Norhanizan, Usaizan; Akmal, Raffi (Faculty of Science and Mathematics, Universiti Pendidikan Sultan Idris (UPSI), 2023)
The discovery of antibacterial drugs from natural sources as a substitute for preventing bacterial resistance has become necessary due to the increase in bacterial drug resistance. Chromolaena odorata has been reported to have antibacterial effects. Therefore, this study investigated the phytochemical components and antibacterial properties of C. odorata leaves. C. odorata leaves were collected, prepared, and extracted using a standard procedure with 95% methanol and 95% ethanol, respectively. Both extracts were subjected to phytochemical screening and Gas Chromatography-Mass Spectrometry to detect phytochemical compounds. Chromolaena odorata methanolic extract at a concentration of 50 mg/mL, 100 mg/mL, 150 mg/mL and 200 mg/mL was carried out for antibacterial screening using the agar well diffusion tested on Staphylococcus aureus (ATCC 43330), Bacillus subtilis (B29), Escherichia coli (ATCC 25922) and Pseudomonas aeruginosa (ATCC 15442). The methanolic extract was present with tannin, terpenoid, alkaloid, and saponin while ethanolic extract was present with tannin and alkaloid. The GC-MS chromatogram identified as many as 27 and 19 compounds for ethanolic and methanolic extract, respectively. The C. odorata ethanolic extract consists mainly of Phenol (0.51%), Sesquiterpenoid (20.69%) and Fatty acid (39.2%). Meanwhile, C. odorata methanolic extract consists of Sesquiterpenoid (62.26%) and Fatty acid (17.11%). Antibacterial activity of S. aureus was the highest inhibition zone diameter with 7.67 mm to 10.33 mm from 50 mg/ml to 200 mg/mL concentration of C. odorata extract. Escherichia coli and B. subtilis inhibition zones diameter was 200 mg/mL concentration of C. odorata extract. No antibacterial activities were obtained for P. aeruginosa. This study suggests that C. odorata consists of a variety of phytochemicals and contains antibacterial properties. Thus, C. odorata represents a promising natural source for antibacterial resistance drugs.